2023
DOI: 10.3390/educsci13020134
|View full text |Cite
|
Sign up to set email alerts
|

Use of Arduino in Primary Education: A Systematic Review

Abstract: In the last two decades, technological advances have been spectacular, and their transcendence has touched all areas of society. Specifically, in the field of education, these advances have allowed projects and approaches such as computational thinking to be taken up more strongly through interdisciplinary visions such as the STEM subjects and technological devices such as Arduino. The main objective of this article is to analyse the uses of Arduino and the achievements it has attained at primary-education lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…Furthermore, across the three learning units, it seems that modular boards have a greater impact on coding. These findings are consistent with studies emphasizing the advantages of Arduino applications in programming (e.g., [31]). Additionally, the utilization of pre-assembled circuits from modular boards and programming Arduino Uno using the user-friendly Arduino IDE software (v1.8.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, across the three learning units, it seems that modular boards have a greater impact on coding. These findings are consistent with studies emphasizing the advantages of Arduino applications in programming (e.g., [31]). Additionally, the utilization of pre-assembled circuits from modular boards and programming Arduino Uno using the user-friendly Arduino IDE software (v1.8.…”
Section: Discussionsupporting
confidence: 91%
“…Active student participation in the learning process can enhance their performance, particularly when it involves inquiry-based learning within a laboratory setting [29][30][31][32][33][34][35]. In recent years, the utilization of Arduino boards in this context has grown, with researchers and educators incorporating them as a useful tool across a broad spectrum of activities and fields [36,37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arduino, with its open-source platform (O'Sullivan & Igoe, 2004), user-friendly interface (Thompson, 2011), and limitless creative potential, serves as a valuable tool for STEM education (e.g. García-Tudela & Marín-Marín, 2023;Plaza et al, 2018). Regarding knowledge comprehension, research demonstrated the usefulness of Arduino and 3D printing in teaching STEM concepts in educational robotics classes (Souza & Sato, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…By promoting the integration of natural sciences, technology, engineering, and mathematics, this methodology seeks to develop in students a deeper and more complete understanding of natural and technological phenomena and the skills necessary to design, build, and program solutions to complex problems. (Akiri, Tal, Peretz, Dori, & Judy, 2020) (Lena, Lauer, Kuhn, Wehn, & Ulber, 2023) (García-Tudela & Marín-Marín, 2023 One of the main benefits of STEM methodologies is that they provide education more relevant to students' daily lives, allowing them to better explore and understand the world around them. In addition, this methodology encourages teamwork, collaboration, and creative thinking, essential skills for success in professional and personal life.…”
mentioning
confidence: 99%